Active and passive cooling technologies for thermal management of avionics in helicopters: Loop heat pipes and mini-Vapor Cycle System. (March 2018) - Zilio, Claudio; Righetti, Giulia; Mancin, Simone; Hodot, Romain; Sarno, Claude; Pomme, Vincent; Truffart, Bertrand
Highlights: An electronic cooling prototype especially designed for helicopter avionics thermal management was realized and tested. A mini-VCS coupled with a miniaturized LHP was used to cool down a hot spot of an avionic card. The thermal management system was tested at different ambient conditions. The results allow full exploitation of the potential of the proposed technology in a typical airborne scenario. Abstract: This paper presents the development of a new electronic cooling concept especially conceived for helicopter avionics thermal management in the framework of 7 th FP EU project TOICA (Thermal Overall Integrated Conception of Aircraft, www.toica-fp7.eu ). A prototype was developed and tested. It consists of a hybrid active-passive cooling system that combines a compact loop heat pipe (LHP) specifically designed for the hot spot treatment at blade level and an air cooled mini-Vapor Cycle System (mini-VCS), which is devoted to the overall heat rejection. This paper presents in details the design and the experimental assessment of each of the main components of the innovative cooling system at different operating test conditions. The tests explore the behavior of the LHP and of the integrated system at different hot spot heat loads, from 10 W to 50 W and heat sink temperatures. The results allow full exploitation of the potential of the proposed technology in a typical airborne scenario.